2009
DOI: 10.1044/ssod19.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Suck Predicts Neuromotor Integrity and Developmental Outcomes

Abstract: Neonatal motor behavior predicts both current neurological status and future neurodevelopmental outcomes. For speech pathologists, the earliest observable patterned oromotor behavior is suck. Suck production requires effective coordination of an infant's oral sensorimotor system and is subject to a variety of neuromodulatory inputs. Demonstration and practice of coordinated suck serves as a biomarker for oral feeding skills neural integrity and is being assessed for its relation to neurodevelopmental outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Though there is little data available on the use of oral motor intervention in infants born at or later than 37 weeks gestation, efficacy of oral motor intervention has been demonstrated in preterm infants. For example, in preterm infants receiving gavage feeds, oral motor intervention has been shown to increase non-nutritive sucking pressure and activity (Barlow, Finan, Lee, & Chu, 2008; Poore & Barlow, 2009). This resulted in decreased time to achieve full oral feeds (Lessen, 2011), higher milk transfer rates, and greater volume taken during oral feeds (Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Though there is little data available on the use of oral motor intervention in infants born at or later than 37 weeks gestation, efficacy of oral motor intervention has been demonstrated in preterm infants. For example, in preterm infants receiving gavage feeds, oral motor intervention has been shown to increase non-nutritive sucking pressure and activity (Barlow, Finan, Lee, & Chu, 2008; Poore & Barlow, 2009). This resulted in decreased time to achieve full oral feeds (Lessen, 2011), higher milk transfer rates, and greater volume taken during oral feeds (Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Sucking and swallowing form critical components of the infant’s motor repertoire and are essential for successful feeding, growth, and development 18 . Sucking and swallowing abnormalities in early infancy have long been viewed as potential markers of neonatal brain injury 17,19,20 . Moreover, it has been suggested that prolonged dysphagia or swallowing difficulties in very preterm infants may represent an early marker of undiagnosed brain injury 20 .…”
mentioning
confidence: 99%
“…The neurological controls that support this motor activity are complex and rely upon the integration of cortical, subcortical, brainstem, and cerebellar inputs 20,22,23 . It is generally agreed that neonatal brain injury can damage these neural pathways, with resultant sucking and swallowing problems 19,20,23,24 . However, there is currently limited evidence regarding this concurrent relation, in particular the frequency of occurrence and the specific patterns of early sucking and swallowing abnormalities associated with different types of neonatal brain injury.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The complex skills, required for the development of sucking and feeding in infants, have been well documented (Bingham et al, 2010;Dodrill et al, 2008a;Pickler et al, 2006;Poore and Barlow, 2009). For the preterm infant acquisition of these skills means dealing with many added challenges depending on the extent of the prematurity and the myriad of accompanying co-morbidities and experiences encountered on the journey through the Neonatal Intensive Care Unit (NICU).…”
Section: Introductionmentioning
confidence: 99%